Analisis Kesalahan Berbahasa Pada Media Iklan Makanan Di Instagram (Kajian Fonologi Dan Morfologi) - Lisna Lestari; Ghina Ayu Salsabila; Wapa Kamilatul Huda; Aveny Septi Astriani (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study is to identify and analyze language errors in food advertisements on Instagram, particularly those related to phonological and morphological errors. The study was conducted by collecting samples of food advertisements on Instagram using a descriptive qualitative method. The data used in this study were words and phrases from Instagram food advertisements that had phonological or morphological errors. Data were collected through the observation and note-taking technique. The results of the study showed that there were phonological and morphological errors in the language. The most common error was the use of italics in foreign languages. The results of this study are expected to be used as one example of a language error case, particularly in the field of phonology and morphology.